Pengembangan Komoditas Pertanian Berbasis Kesesuaian Lahan di Kecamatan Alor Tengah Utara Kabupaten Alor - Nalle, Margiman S.; Lanya, Indayati; Trigunasih, Ni Made (Agrotrop : Journal on Agriculture Science; Vol 13 No 3 (2023)DO - 10.24843/AJoAS.2023.v13.i03.p01, 2023)
Agricultural Commodity Development Based on Land Suitability in The District of Alor Central North Alor Regency . The development of agricultural commodities in Alor Regency is ased on land suitability. This study aims to analyze/land quality, analyze and create land use class maps, analyze farming priorities, create commodity zoning maps, and land use direction maps. Agricultural commodities include upland rice, corn, cassava, red chilies, tomatoes, robusta coffee, cocoa and cashew nuts. Using survey methods based on field observations, field and laboratory data, spatial analysis using remote sensing and information systems, land classification using land characteristics/quality methods with plant growing conditions. Commodity zoning and directions for agricultural land use by class based on the highest land, and existing land use. Feasibility of use with the calculation of the B/C Ratio. The results showed that the potential for upland rice, cassava, robusta coffee and cocoa were classified as marginally appropriate classes (S3wa12rc13), while corn, red chili, tomatoes, and cashew nuts were classified as quite appropriate classes (S2tcwa1lp12). Limiting factors include temperature, air availability, rooting media, and land preparation. The zoning of commodities in each land map unit includes corn, red chilies, tomatoes, and cashews. Directions for land use in mixed gardens, dry fields, paddy fields and rainfed rice fields are considered for the development of agricultural commodities with monoculture and polyculture cropping patterns. The B/C Ratio shows that agricultural commodities are feasible to be developed in North Central Alor District.